ミクログリアのストレス応答を担う転写制御機構 - 谷口, 将之; 古屋敷, 智之 (日本薬理学会年会要旨集, 2022)
Clinical and rodent studies have suggested the role of microglial activation for stress pathology of mental illness. However, the nature of microglial stress response remains unknown. Using single-cell RNA-seq of microglia isolated from multiple brain areas in mice, we found that microglial transcriptomes manifested the brain region-specificity and individual variability of stress susceptibility after chronic social stress. Deeper transcriptome analyses of microglia from the medial prefrontal cortex and nucleus accumbens segregated gene clusters of brain region-specific (local) and non-specific (global) responses to chronic social stress, and the global responses encoded individual variability of stress susceptibility. Epigenomic analyses with ChIP-seq and ATAC-seq predicted distinct transcription factors involved in the respective responses, and surgical and genetic manipulations identified a peripheral stress signal that induced the global transcriptional responses to confer microglia with stress susceptibility. These findings suggest that microglia integrate local and global stress signals via transcriptional machinery to determine its activation state and behavioral consequences. In this symposium, I will introduce these recent findings and discuss their relevance to mental illness pathology.